PERSEPSI ANGGOTA KELOMPOK TANI TERHADAP UNIT PENGOLAHAN HASIL (UPH) KOPI PADA KOPERASI KAGHO MASADI DESA RADA BATA KECAMATAN GOLEWA KABUPATEN NGADA - Sebastianus Wogha; Fidelis Klau; Mustafa Abdurrachman (Buletin Ilmiah Impas, 2021)
This research has been carried out at the Kagho mass processing unit (UPH) which has three farmer groups with members of their farmer groups coming from three villages, this research was conducted in July 2019. The purpose of this study was to determine: (1) How to process coffee in The coffee yield processing unit (UPH) in the Kagho cooperative, the Radabata village, Golewa sub-district, Ngada district, (2) Perceptions of farmer group members towards the Coffee Produce Processing Unit (UPH) in the Kagho cooperative, Golewa District, Ngada Regency. The method used in this research is a survey method. Determination of respondents using a census, namely by taking 43 members of UPH Kagho, the mass data collected were primary data and secondary data. The results showed that the processing method for Arabica coffee in the UPH Kagho Masa Cooperative, Radabata Village, Golewa District, Ngada Regency was carried out in accordance with the applicable Production Operational Standards (SOP) where the Production Operational Standard included picking coffee cherries, sorting coffee cherries, peeling fruit skins, washing. , fermentation, coffee bean drying, roasting and milling, packaging / packing, and marketing. So that the aroma and taste of coffee are maintained. Farmers' perception of the role of Coffee Processing Unit (UPH) in Kagho Masa Cooperative in coffee farming in Radabata Village Golewa DistrictNgadaDistrict, grouped very well with the achievement of a maximum score of 94.83%. while the farmer's perception of the processing of the result is very good with the achievement of a maximum score of 91.86%.